A national analysis of the pharmacy workforce in Indonesia - Sherly Meilianti; Felicity Smith; Franciscus Kristianto; Roy Himawan; Desak Ketut Ernawati; Rasta Naya; Ian Bates (BMC, 2022)
Abstract Background Pharmacists play a fundamental role in healthcare systems and achieving Universal Health Coverage (UHC) through quality primary healthcare service provision. While the World Health Organization (WHO) forecasts a global shortage of health workforce by 2030, mainly affecting low- and middle-income nations (LMICs), limited published literature is found regarding pharmacy workforce capacity in LMICs, including Indonesia. This paper aims to analyse pharmacists' capacity in Indonesia to identify emerging workforce planning gaps for future workforce planning and policies in Indonesia. Method Several data sources were accessed, including a database from the National Pharmacy Committee and the professional leadership body in Indonesia. Descriptive (frequencies, percentages, and mean), correlational and time-series analysis using curve estimation were conducted. Secondary data on the number of programmes, pharmacy students, pharmacy workforce (pharmacists and pharmacy technicians) per province were obtained from the Ministry websites and reports. Result There were a total of 77 191 registered pharmacists in Indonesia in 2019. The pharmacists' pyramid showed a youth bulge as a general indication of market expansion in the education sector correlating to the pharmacy programme's number and size. There was a variation in pharmacy workforce density and access to pharmacy programmes across islands, which also were strongly correlated. Forecasting estimates that by 2030, women will represent around 86% of pharmacists in Indonesia. More female pharmacists were found working in the hospital and primary healthcare (providing direct services to patients) than male pharmacists. Younger pharmacists worked in the industrial sector, while older pharmacists worked in governmental and educational institutions. Conclusion This study signposted workforce planning gaps for policy development in Indonesia, including a need to develop structured training to support early career pharmacists in their practice. There is also a need for better access to professional development programmes designed to support female pharmacists return to the regulated workforce following career breaks. National policy to promote equitable distribution and retention of pharmacists is recommended.